Alpha-mangostin reduces cell viability in sorafenib-surviving cells by modulating multiple drug transporters in HepG2 hepatocellular carcinoma cells - Vincent Kharisma Wangsaputra, Syarinta Adenina, Melva Louisa (Journal of Applied Pharmaceutical Science, 2021)
A previous study showed that alpha-mangostin (AM) showed benefit when given to sorafenib (SOR)-surviving cells. However, the mechanism was not fully understood. The present study aimed to understand the effect of AM on SOR-surviving cells and its agent concerning drug transporters. SOR-surviving cells were treated with SOR 10 μM. Surviving cells were divided into four groups of treatment, namely, vehicle only dimethyl sulfoxide (DMSO), SOR 10 μM, AM 20 μM, or combination of SOR 10 μM-AM 20 μM. As controls, HepG2 naïve cells were treated with DMSO only or AM 20 μM. Cell viability was counted using trypan blue exclusion assay. Simultaneously, the mRNA expressions of P-glycoprotein (P-gp), ABCG2, MRP2, MRP3, OCT1, and OATP1B3 drug transporters were examined with quantitative reverse transcriptase-polymerase chain reaction. Decreased mRNA expression of P-gp was found in SOR-surviving cells treated with SOR. In contrast, AM alone or SOR's combination caused a significant increase in both efflux and influx transporters, no difference in fold increase of all transporters evaluated in AM versus SOR-AM combinations. Generally, AM treatment increased the mRNA expression of all the drug transporters.
Keywords: Alpha-mangostin, sorafenib resistance, drug transporters, P-glycoprotein, OCT1.